Implementing Velocity-Based Training to Optimize Return to Sprint After Anterior Cruciate Ligament Reconstruction in Soccer Players: A Clinical Commentary - Florian FORELLI; Jérôme RIERA; Patrice MARINE; Maxime GASPAR; Geoffrey MEMAIN; Nicholas MIRAGLIA; Mathias NIELSEN – LE ROUX; Ismail BOUZEKRAOUI ALAOUI; Georgios KAKAVAS; Timothy E HEWETT; Enda KING; Alexandre JM RAMBAUD (International Journal of Sports Physical Therapy)
After anterior cruciate ligament reconstruction (ACLR), return to sprint is poorly documented in the literature. In soccer, return to sprint is an essential component of return to play and performance after ACLR. The characteristics of running in soccer are specific (velocity differences, nonlinear, intensity). It is important to address these particularities, such as curvilinear running, acceleration, deceleration, changes of direction, and variations in velocity, in the patient's rehabilitation program. Force, velocity, and acceleration capacities are key elements to sprint performance. Velocity-based training (VBT) has gained much interest in recent years and may have a role to play in optimizing return to play and return to sprint after ACLR. Force, velocity, and acceleration can be assessed using force-velocity-power and acceleration-speed profiles, which should inform rehabilitation. The purpose of this commentary is to describe a velocity-based return to sprint program which can be used during ACLR rehabilitation.